2016
DOI: 10.1039/c6ob00678g
|View full text |Cite
|
Sign up to set email alerts
|

Directing activator-assisted regio- and oxidation state-selective aerobic oxidation of secondary C(sp3)–H bonds in aliphatic alcohols

Abstract: The regioselective conversion of an unactivated C(sp(3))-H bond of a methylene carbon (CH2) into a C-O single bond is an attractive reaction in organic synthesis. Herein, we present a strategy for a regio- and oxidation state-selective aerobic C-H oxidation based on an N-hydroxyamide-derived directing activator (DA), which is attached to a hydroxy group in alcohol substrates. The DA reacts with NOx species generated in situ from NaNO2, a Brønsted acid, and aerobic oxygen, and effectively generates an amidoxyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
0
8
0
2
Order By: Relevance
“…Moreover,l ow conversions are typically observed. [111] This method provided predominantly the nitrate esters with significant amounts of ketone present. [110] Oxygenation of benzylic,p ropargylic,t ertiary and secondary CÀHb onds with good regioselectivity for the g and d position depending on the substrate was possible.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover,l ow conversions are typically observed. [111] This method provided predominantly the nitrate esters with significant amounts of ketone present. [110] Oxygenation of benzylic,p ropargylic,t ertiary and secondary CÀHb onds with good regioselectivity for the g and d position depending on the substrate was possible.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Co(OAc) 2 was used as acocatalyst either in combination with catalytic Mn(OAc) 3 •2 H 2 Oo r, in the case of tertiary CÀH bonds,stoichiometric Me 2 S, which acts as areductant for the initially formed hydroperoxides.I nafollow-up paper they proposed am etal-free alternative using superstoichiometric NaNO 2 in combination with an acid activator. [111] This method provided predominantly the nitrate esters with significant amounts of ketone present. Thed irecting activator can be removed by reduction with LiAlH 4 ,with concomitant reduction of the ketone,resulting in the formation of 1,3-diols.…”
Section: Organocatalysismentioning
confidence: 99%
“…125 Also in 2016, the Oisaki and Kanai group showed that these radical precursor scaffolds can be combined with in situ generated NO x species to form γ-nitrated alcohols. 126…”
Section: Scheme 20 δ C-h Oxygenation Via In Situ Oxime-derived Radicalsmentioning
confidence: 99%
“…In einer auf diesen Ergebnissen aufbauenden Arbeit schlugen die Autoren eine metallfreie Alternative vor, in der sie überstçchiometrische Mengen an NaNO 2 in Kombination mit einer Säure als Aktivator einsetzten. [111] Dabei wurden hauptsächlich die Nitratester und signifikante Mengen der Ketone erhalten. Der DA kann durch Reduktion mit LiAlH 4 abgespalten werden, wobei gleichzeitig das Keton reduziert wird und so 1,3-Diole erhalten werden.…”
Section: Organokatalyseunclassified